Comparison of Two Different Threshold Values for the Measurement of Gastric Residual Volume on Enteral Nutrition Support in the Neurocritically Ill Patients - Liu, Fang; Liu, Gang; Sun, Rui; Wang, Jinli; Li, Miao; Gong, Lichao; Su, Yingying; Zhang, Yan; Wang, Yuan (Frontiers in Nutrition, 2022)
Background: Although recommendations on gastric residual volume (GRV) have been applied to clinical practice of intubated patients, evidence-based data about the GRV of neurocritically ill patients are still lacking. We conducted this study to investigate the safety of increased GRV in neurocritically ill patients on enteral nutrition (EN) support. Methods: Neurocritically ill patients feeding through intragastric enteral tubes were recruited consecutively between July 2018 and June 2021. Patients were divided into a control group (GRV 100 ml) and a study group (GRV 200 ml). Demographic data, admission diagnosis, and severity scores were collected from the patient medical records. The frequency of diet volume ratio (diet received/diet prescribed), incidence of gastrointestinal complications, and outcome variables were evaluated. Results: There were 344 patients enrolled, of whom 197 had mechanical ventilation support. High GRV events in the control group were more frequent than those in the study group (38.1% vs. 22.8%, p=0.002). The total gastrointestinal complication rate did not differ significantly between the two groups (study group: 61.1%, 102/167 vs. control group: 67.9%, 114/168). In the study group, two patients had aspiration (1.2% vs. 0%, p=0.245). The study group showed a superior diet volume ratio but the difference was not significant. The outcomes of the study group were slightly better than those of the control group; however, no significant differences were observed between the two groups with respect to length of stay in the neurointensive care unit (19.5 days vs. 25.3 days) and mortality (10.8% vs. 14.9%) at discharge. Conclusion: Our results suggest that 200 ml may be a safe normal limit for GRV in neurocritically ill patients.